2020
DOI: 10.1017/s1537592720002200
|View full text |Cite
|
Sign up to set email alerts
|

Submerged for Some? Government Visibility, Race, and American Political Trust

Abstract: Scholarship concerning American government visibility has focused on the state’s growing submergence, yet these accounts contrast with racial and ethnic politics research focusing on the American state’s conspicuousness in the lives of people of color. Attending to this disconnect, I ask how government visibility varies across racial groups. Combining interviews and quantitative analysis within a policy feedback framework, I argue that five public policy trends have created a racial split in the American state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…It is not clear why diabetes status might have more of a mobilizing relationship in these groups. However, recent work indicates that negative perceptions of community disadvantages or inequality are associated with higher likelihood of political participation (Corcoran et al, 2015) and that experiences with government or government visibility may shape political trust and influence participation (Rosenthal, 2020). These studies suggest some groups in poor health may elect to participate in politics as a result of the current political context or that perceived community health disadvantages may also play a role in likelihood of voter turnout.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why diabetes status might have more of a mobilizing relationship in these groups. However, recent work indicates that negative perceptions of community disadvantages or inequality are associated with higher likelihood of political participation (Corcoran et al, 2015) and that experiences with government or government visibility may shape political trust and influence participation (Rosenthal, 2020). These studies suggest some groups in poor health may elect to participate in politics as a result of the current political context or that perceived community health disadvantages may also play a role in likelihood of voter turnout.…”
Section: Discussionmentioning
confidence: 99%
“…Field research can be used to interpret and evaluate frameworks, often with interview questions based on the same existing literature that informs survey instrumentation. But in-depth interviews are more instructive than surveys when interviewee accounts do not align with expectations stemming from the extant scholarship (Rosenthal 2020). In these instances, researchers can observe patterns in what interviewees say not only to critique the literature, but also to innovate or deepen theory and conceptualization.…”
Section: Evidence Methods and Racial And Ethnic Politicsmentioning
confidence: 99%
“…As recent studies (Cohen and Luttig 2020;Weaver, Prowse, and Piston 2019) have demonstrated, members of marginalized minority groups often have much deeper knowledge of how the U.S. government has worked against them rather than for them. As a result of their power to control and regulate people, some government institutions are also more visible to these groups than they are to whites (Rosenthal 2020;Michener, SoRelle, and Thurston 2020). Minorities too often see the most menacing face of these institutions and experience the most broken parts of American democracy.…”
Section: Evidence Methods and Racial And Ethnic Politicsmentioning
confidence: 99%
“…While government distrust is historically low in contemporary America (Raine, Keeter, and Perrin 2019), it is important to recognize that its roots differ across racial groups. Levels of trust in government among Black Americans are specifically tied to attitudes about the police (Rosenthal 2020). This connection between distrust and the police becomes clear when listening to Black views on vaccines, as seen in this excerpt from another focus group participant: "Everybody is on high alert, in the black community… very distrusting, because we don't know what's going to be perpetrated against us… You see what's going on with police brutality and things, things have been caught on tape and it's not being addressed, so [it's not so] weird in thinking that the vaccines that go to zip codes 19131, 19139, 19103 would be tainted or just-it's just that that paranoia, but there's substance to the paranoia" (Momplaisir et al 2021, 6).…”
Section: Introductionmentioning
confidence: 99%
“…The face of government in most ordinary African-Americans' daily lives is one of deceit, intimidation, coercion, and sometimes death" (Taylor 2021). And while this coercive face of government may take many forms in Black communities, the police stand out as the most consistent and visible (Rosenthal 2020;Soss and Weaver 2017), including in recent discriminatory enforcement of pandemic-related guidelines (Southall 2020;Dunbar and Jones 2021). As former Attorney General Loretta Lynch put it, for many Black Americans, "the police are the only face of government they see" (2015).…”
mentioning
confidence: 99%